Lesbian, Gays, Bisexuals, Transgendered, and Queer (LGBTQ) People and Adult Education: An Examination of Literature in Adult Education 2010-2020 - Lisa Baumgartner; Lauren Chaney; Humberto de Faria Santos; Steven Schmidt (Adult Education Research Conference, 2022)
We discuss our review of LGBTQ issues in adult education journals between 2010 and 2020. We pose several topics for discussion based on our findings.
Keywords: LGBTQ; literature review; adult education